Opioid Addiction/Pregnancy and Neonatal Abstinence Syndrome (NAS): A Preliminary Open-Label Study of Buprenorphine Maintenance and Drug Use Targeted Psychotherapy (DUST) on Cessation of Addictive Drug Use - Tabi, Sarah; Heitner, Sarah A.; Shivale, Swati; Minchenberg, Scott; Faraone, Stephen V.; Johnson, Brian (Frontiers in Psychiatry, 2020)
Background: Neonatal abstinence syndrome (NAS) is common, expensive, and hurts opioid addicted women and their families. Current treatments do not sufficiently address comorbid addictions, especially tobacco use, among pregnant buprenorphine-maintained women. Methods: 25 consecutive admissions of pregnant, opioid addicted women were treated with buprenorphine maintenance and a novel intervention for pregnant opioid addicted patients, Drug Use Targeted Therapy (DUST). DUST entails a combination of informing women about the impact of various drugs on their fetus, discussing the woman’s thinking about these consequences of drug use, and varying the frequency of psychotherapy; increasing if addictive drugs are used and decreasing if the woman wishes when drug use is stopped. Results: 20/25 remained in treatment until delivery. All 20 women were using addictive drugs at admission. None were planned pregnancies. There was a high prevalence of emotional, physical or sexual abuse, criminal behavior, comorbid psychiatric disorders, and chronic pain. Nineteen stopped all addictive drugs. NAS was present for 5 out of 19 newborns with a duration of hospitalization from 4 – 6 days. Conclusions: This preliminary open-label case series found that pregnant buprenorphine maintained women can stop tobacco. What has sometimes been termed “neonatal opioid abstinence syndrome” may most accurately be termed, “neonatal opioid/tobacco abstinence syndrome.” If the treatment effectively addresses tobacco use, other addictive drugs are rarely used. DUST resulted in a 95% quit rate for addictive drugs. Pilot data on this new intervention is limited; a case series that does not have a corresponding control group.